Investment Knowledge, Self Efficacy, Expected Return, Perceived Risk dan Minat Mahasiswa Berinvestasi Saham - Wijaya Putri, Ni Putu Jessica Anggi; Dwi Ratnadi, Ni Made (E-Jurnal Akuntansi, 2023)
The aim of the research is to empirically prove the influence of investment knowledge, self-efficacy, expected return and perceived risk on students' interest in investing in shares. The population is active students of the Accounting and Management undergraduate study program at the Faculty of Economics and Business, Udayana University. Samples were taken using the proportional stratified random sampling method, obtaining 300 students as respondents. The data analysis technique uses Structural Equation Model-Partial Least Square (SEM-PLS). The results of the analysis show that investment knowledge, self-efficacy, and perceived risk have a positive effect on students' interest in investing in shares. Meanwhile, expected return has no effect on students' interest in investing in shares. Keywords: Interests, Investment Knowledge, Self Efficacy, Expected Return, Perceived Risk